Surgery of the Skull Base Practical Diagnosis and Therapy (Springer International Publishing, 2018)
This book discusses all aspects of skull base surgery, from a neurosurgical point of view. The therapeutic options in the treatment of skull base lesions are explained and a systematic overview of relevant diseases is included. A strong emphasis is placed on practical aspects of skull base surgery: classic surgical approaches and also methods where there has been rapid recent development, such as stereotactic radiation therapy and interventional neuroradiology. Several international specialists systematically describe the treatment of traumatic lesions, tumors, vascular lesions, and developmental anomalies. Surgery of the Skull Base is aimed at neurosurgeons, ENT surgeons, maxillofacial surgeons, neurologists, and radiologists.